Can the Labor Demand Curve Explain Job Polarization? - Andreas Peichl; Martin Popp (Institute of Labor Economics (IZA), 2022)
In recent decades, many industrialized economies have witnessed a pattern of job polarization. While shifts in labor demand, namely routinization or offshoring, constitute conventional explanations for job polarization, there is little research on whether shifts in labor supply along the labor demand curve may equally result in job polarization. In this study, we assess the impact of labor supply shifts on job polarization. To this end, we determine unconditional wage elasticities of labor demand from a unique estimation of a profit-maximization model on linked employer-employee data from Germany. Unlike standard practice, we explicitly allow for variations in output and find that negative scale effects matter. Both for a skill- and a novel task-based division of the workforce, our elasticity estimates show that supply shifts from immigration and a decline in collective bargaining successfully explain occupational employment patterns during the 1990s.
Keywords: J23; J31; D22; L60; 330; labor demand; job polarization; skills; tasks